Antidepressant medicines for the elderly: are we using them appropriately? - Amar, K; Wilcock, G (1994)
We monitored antidepressant prescriptions to elderly patients over the age of 60 years admitted to a teaching hospital over a 3-months period. During this time we identified 48 patients taking antidepressant medication of whom 18 were started in hospital, the other 30 patients having had their therapy initiated before admission. In the hospital group, 1 in 3 was probably not depressed, as judged by using (Brief Assessment Scale Depression Cards), despite this screening having been made within 1 week of starting treatment. In the second group, i.e., those in whom treatment had been initiated before admission, 50% were still depressed in spite of prolonged treatment. We conclude that elderly patients should only be started on antidepressant therapy after careful assessment, and when prolonged treatment is considered necessary, it should be regularly evaluated for efficacy and psychiatric advice sought for those who fail to respond.